KARAKTERISASI SIFAT FISIK, KIMIA DAN SENSORIS BIHUN BERBAHAN TEPUNG KOMPOSIT GANYONG (Canna edulis) DAN KACANG HIJAU (Vigna radiata) - Jumanah Jumanah; Wiwik Siti Windrati; Maryanto Maryanto (Faculty of Agricultural Technology, University of Jember, 2017)
Vermicelli is a processed product with yarn forms which are made from rice flour. Canna flour can replace the main ingredient of rice flour in making vermicelli. The manufacture of vermicelli flour composite requires protein ingredients such as mung bean flour to increase the protein content of vermicelli. The purpose of this study is to determine the good ratio of manufacture of vermicelli made from canna and mung bean composite flour and knowing the best formulation based on the most preferred of vermicelli. The research is using Completely Random Design (CRD) one factor method that is canna flour and mung bean flour substitution with five variations treatments that is Controls (vermicelli rice commercial), P1 (60%:5%:35%), P2 (50%:15%:35%), P3 (40%:25%:35%), P4 (30%:35%:35%), P5 (20%:45%:35%). This research results indicate that the of canna flour and mung bean ratio effected on ash content, fat content, protein content, carbohydrate, color, rehydration, elasticity and organoleptic , but did not effected on moisture content, taste, flavor and overall. Vermicelli favored pains on P4 treatment (30%: 35%: 35%) produced had value of preferences color 5.46 (netral), flavor 5.46 (neutral), taste 5.23 (nettral), texture 5.92 (netral), overall 5.92. Chemical properties of moisture content 9.85%, ash content 0.05%, fat content 1.74%, protein content 9.83%, carbohydrate content 78.60%, and color (lightness) 54,94 , elasticity 7.32 %and power of Rehydration 24.77%. Keywords: vermicelli, canna flour, mung bean flour, tapioca